Determination of age and sex using bimastoid diameter : a cone beam computed tomography study = Deteminación de la edad y el sexo mediante el diámetro bimastoide : un estudio en tomografía computarizada de haz cónico (CBCT) - Okumuş, Özlem
This study aimed to investigate the possibility of age and sex determination using bimastoid diameter with cone-beam computed tomography (CBCT). This retrospective study investigated 100 female and 100 male patients aged 18-83 years (mean age: 45.55±16.28 years). To measure bimastoid diameter, the appropriate image was chosen from sagittal, coronal, and axial images of CBCT in which the measurement points could be best detected. The distance between the points of the mastoid process was measured using three-dimensional coronal reconstruction. The mean bimastoid breadth was 106.12±6.22mm. The bimastoid diameter in male cases was higher than that in female cases (110.69±4.53mm vs. 101.65±4.00mm). There was no significant difference in bimastoid breadth with advancing age. For sex determination, morphometric measurements of bimastoid diameter ensured a high rate of dimorphism in the Turkish subpopulation. CBCT morphometric analysis may be reliable and convenient for evaluating sex and may be recommended to compare population data.